2015
DOI: 10.1002/mus.24631
|View full text |Cite
|
Sign up to set email alerts
|

Flexor carpi radialis surface electromyography electrode placement for evoked and voluntary measures

Abstract: The electrode placement resulted in reliable measures from voluntary contractions and CMAPs. Normalization can decrease reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
(138 reference statements)
0
16
0
Order By: Relevance
“…The lack of stability, as assess by the repeated-measures ANOVA, resulted in a reduced intraclass correlation coefficient. However, the intrasubject coefficient of variation (Grand Mean/SEM) was 24.5%, which was deemed acceptable for further analyses (Green et al 2015). …”
Section: Resultsmentioning
confidence: 99%
“…The lack of stability, as assess by the repeated-measures ANOVA, resulted in a reduced intraclass correlation coefficient. However, the intrasubject coefficient of variation (Grand Mean/SEM) was 24.5%, which was deemed acceptable for further analyses (Green et al 2015). …”
Section: Resultsmentioning
confidence: 99%
“…The effect that electrode placement has on the patterns of responses measured by CMAP34573637383940 and electromyography (EMG)414243444546 requires ad hoc adjustments to maximize data reliability and validity. In this paper, we showed that the reliability of EIM as a biomarker for the assessment of muscle is also affected by the precise positioning of the electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…The point that elicited the largest sEMG response at the lowest stimulation intensity was identified as the motor point. Electrodes were placed in a bipolar electrode configuration, as it is reliable for both evoked and voluntary measures [ 23 ], one on the electrically identified motor point, and the other placed immediately distal (10 mm). The electrodes were secured to the skin surface with two-sided tape and electrolyte gel (Signa Gel®, Parker Laboratories, Fairfield, USA).…”
Section: Methodsmentioning
confidence: 99%
“…These data suggest that neuromuscular function during hyperthermia is dependent on both the source of thermal stimuli and the type of task being performed. Surface electromyograpy (sEMG) is a non-invasive method to objectively quantify neuromuscular activation of muscle [ 23 ], and could be a valuable technique to investigate the physiological mechanisms responsible for these differences. Additionally, sEMG has been used extensively to investigate various neuromuscular disorders [ 24 ], muscular fatigue [ 9 , 25 27 ], and the effects of temperature on muscle properties [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%